Impact of baobab (Adansonia digitata L) fruit pulp consumption on hemoglobin and iron status in Kenyan schoolchildren: A randomized, controlled trial - Evang, Esther C.; Justus Liebig University Giessen (My University, 2021)
In the Kenyan diet, bioavailability of iron is low and predisposes the population to iron deficiency. Prevalence of anemia and iron deficiency is high, particularly in food-insecure settings. Fruit pulp of the indigenous baobab is rich in minerals and trace elements and contains significant amounts of vitamin C, which enhances non-heme iron bioavailability. The objectives of this dissertation were 1) to compare malnutrition and micronutrient deficiencies linked to dietary intake among urban and rural Kenyan schoolchildren to identify the population that benefits most from a nutrition intervention with baobab fruit pulp (BFP) and 2) to determine the impact of BFP consumption on the hemoglobin (Hb) levels and iron status of schoolchildren. Among school children aged 6-12 years in an urban resource-poor setting in Nairobi (in 2017) and in a rural setting in Kiuti (in 2018), apparently healthy children were screened to exclude undernourished children (according to mid-upper arm circumference) and include children with lowest Hb levels. The single-blind randomized controlled Baobab Nutrition Intervention Study was implemented over a period of 12 weeks in the rural setting. Children in the intervention group received a drink with BFP, while the control group received an isoenergy drink without BFP. Both groups consumed the drinks in addition to a modified school meal (local dish, mix of maize and beans). At baseline and endline, registered nurses took blood samples to determine Hb, ferritin (FER), soluble transferrin receptor (sTfR), zinc, C-reactive protein (CRP), and acidic glycoprotein (AGP). Furthermore, the children’s weight and height were assessed. Hb disorders (sickle cell and α-thalassemia trait) were assessed only at baseline. During the 12-week intervention, dietary intake was accessed with 24 h –recalls in the first (t1), fifth (t2), and eleventh (t3) week. Nutrient intake was estimated with the software NutriSurvey, and nutrient adequacy ratio was determined by applying the Kenyan recommended dietary allowance. For urban/rural comparison, baseline data of a subgroup of children aged 7-9 years was used. Among the 36 urban and 35 rural children, the prevalence of moderate underweight, wasting, and stunting were lower in urban than in rural children, with significant differences in median z-scores for underweight (p < 0.001) and wasting (p = 0.001). Significantly higher values for serum ferritin (p = 0.012) and zinc (p < 0.001) were found in urban children. Nonetheless, the median adequacy ratios were higher for vitamin C (p = 0.045), iron (p = 0.003), and zinc (p = 0.003) in rural than in urban children. In conclusion, the low intake of nutrients in the urban setting was of greater concern than nutrient bioavailability, and vice versa in the rural setting. Hence, the benefits of addressing iron bioavailability were higher in the rural than in the urban setting. In the Baobab Nutrition Intervention Study, 223 rural children participated in the screening, among them 66 were allocated in either intervention or control group and data of 29 children in each group were used for analyses. During the intervention, the intake of vitamin C and calcium were significantly higher in the intervention than in the control group. The development of hemoglobin, FER, and sTfR did not differ significantly between the intervention and control groups. However, in the intervention group, Hb levels improved slightly (2.2%), while they decreased slightly (1.2%) in the control group. Levels of the geometric mean of sTfR remained almost unchanged (0.7%) in the intervention group, and slightly worsened (2.7%) in the control group. In both groups, geometric mean of FER levels decreased, yet to a smaller extent in the intervention (17.3%) than in the control (26.0%) group. Limiting factors on the promoting effect on iron bioavailability might be the inhibitory effect of phytate and polyphenols from the school meal and phytochemicals from BFP itself that did not overcome the promoting effect of BFP. Even though no significant effects of BFP on Hb levels or iron status could be detected in this study, the tendencies of changes are concordant and point towards a beneficial effect of BFP on non-heme iron absorption. The identification of products such as BFP remains pertinent to help improve non-heme iron absorption in the most vulnerable populations, and particularly in food-insecure areas where the indigenous baobab tree and its nutritious fruits are available and affordable. Therefore, integrating BFP into existing national homegrown school meal programs and nutrition education activities are reasonable approaches to prevent childhood anemia and to create awareness for the nutritional benefits of indigenous fruits.
Keywords: Baobab; Anemia; Bioavailability; Schoolchildren; Kenya; nutritional status; micronutrients; dietary intake; randomized controlled trial; nutrition intervention; food insecurity; malnutrition; ddc:610; ddc:630